ASUHAN KEPERAWATAN KELUARGA PADA TAHAP PERKEMBANGAN LANJUT USIA DENGAN MEMBERIKAN JUS NANAS UNTUK MENURUNKAN KADAR ASAM URAT PADA NY. Y - Rahma Suci Safitri,; Alfika safitri,; M. Hasan Basri,; Rina Puspita Sari, (Nusantara Hasana Journal, 2023)
Background : The family is the smallest unit of society consisting of the head of the family and several people who gather and live in a place under one roof in a state of interdependence. Gout or often known as gout arthritis is a disease that attacks the joint area. High uric acid levels are caused by genetic or hereditary factors and lifestyles that often consume foods that contain lots of purines. Many purines are found in organ meats, green vegetables and nuts. Method : Data collection was done by checking uric acid levels first before being given the implementation of uric acid education and pineapple juice, for 5 days they will be given pineapple juice and checked for uric acid levels again on day 3 and 5 after being given pineapple juice. Results : The uric acid level before being given the implementation was (8.2 mg/dL), on the 3rd day after administration of pineapple juice the uric acid level became (7.1 mg/dL) and on the 5th day the uric acid level decreased again (6.1 mg/dL). Conclusion : Provision of pineapple juice is proven to have an effect on reducing uric acid levels in the blood and the importance of managing diet and maintaining a clean and healthy lifestyle.